Respuesta :
Answer:
x=(3e+2d)/(2g-ef)
Step-by-step explanation:
d=e(3+fx)/(2+gx)
or, 2d+2gx=3e+efx
or, 2gx-efx=3e+2d
or, x(2g-ef)=3e+2d
or, x=(3e+2d)/(2g-ef)
Answer:
x = (-2d + 3e) / (dg - fe)
Step-by-step explanation:
We solve it by using algebra.
1. Multiply each side by 2 + gx:
dgx + 2d = fxe + 3e
2. Subtract fxe on both sides:
dgx − fxe + 2d = 3e
3. Subtract 2d from both sides:
dgx − fxe = −2d + 3e
4. Factor out x:
x (dg − fe) = −2d + 3e
5. Divide dg - fe:
x = (-2d + 3e) / (dg - fe)
I hope this helped! :D